2018
DOI: 10.1039/c8ra05150j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual sodium ions on the structure and properties of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)

Abstract: Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is a promising conducting polymer in terms of its applicability to transparent and flexible electronic devices. Generally, a negatively charged PSS chain can interact with alkali metal cations like sodium and potassium. During polymerization, these ions, especially sodium ions, remain in an aqueous state and affect particle formation. This paper describes the effect of residual sodium ions on the synthesis of PEDOT:PSS and its electrical and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…The XPS signals for S 2p at 163–170 eV in the PEDOT:PSS films should be deconvoluted, because: (a) there are multiple peaks for the aromatic S in PEDOT with a binding energy peak at 163–166 eV and the sulfonate form of PSS at 167–170 eV, (b) each of S 2p spectra shows spin-split signals (i.e., S 2p 1/2 and S 2p 3/2 ) with the corresponding ratio of 1:2, (c) the sulfur in PEDOT can be either in a neutral form (S) or in a cationic form (S + ), and (d) the sulfonic acid (i.e., PSSH) and sodium sulfonate (i.e., PSSNa) also have a difference of ~0.4 eV in the binding energy [ 26 , 45 , 48 , 49 ]. Changes in the ratios, examined by XPS, have been correlated with the conductivity increase [ 32 , 45 , 50 ]. In our samples, we found that the sulfonate-to-EDOT ratio was 2.4 for pristine PEDOT:PSS films, similar to the nominal ratio of the stock dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS signals for S 2p at 163–170 eV in the PEDOT:PSS films should be deconvoluted, because: (a) there are multiple peaks for the aromatic S in PEDOT with a binding energy peak at 163–166 eV and the sulfonate form of PSS at 167–170 eV, (b) each of S 2p spectra shows spin-split signals (i.e., S 2p 1/2 and S 2p 3/2 ) with the corresponding ratio of 1:2, (c) the sulfur in PEDOT can be either in a neutral form (S) or in a cationic form (S + ), and (d) the sulfonic acid (i.e., PSSH) and sodium sulfonate (i.e., PSSNa) also have a difference of ~0.4 eV in the binding energy [ 26 , 45 , 48 , 49 ]. Changes in the ratios, examined by XPS, have been correlated with the conductivity increase [ 32 , 45 , 50 ]. In our samples, we found that the sulfonate-to-EDOT ratio was 2.4 for pristine PEDOT:PSS films, similar to the nominal ratio of the stock dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 SO 4 or EG is commonly used as an additive that induces phase separation between PEDOT and PSS 22,23 . When the additives are mixed with PEDOT:PSS, the size of the PEDOT increased as it is aggregated and becomes highly electrically conductive [24][25][26] . In atomic force microscope (AFM) images, it was confirmed in ISHCP-400 that the shape of PEDOT grain was different from other samples, and a linear-like nanofibril acted to improve the connection with PEDOT chains under strain.…”
Section: Resultsmentioning
confidence: 99%
“…The linear PEDOT:PSS structure lowers the intrinsic resistance to particles, and the longer PEDOT chains also lower the resistance, requiring less PEDOT:PSS particle for the same sheet resistance. 15 As a result, the required PEDOT:PSS particle count is reduced in the same sheet resistance, resulting in increased transmittance.…”
Section: Electrical and Optical Properties Of Pedot:pssmentioning
confidence: 99%
“…There is a wide variety of conductive polymers such as polyacetylene, 7 polypyrrole, 8 polythiophene, and poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). 9 Among these, PEDOT:PSS exhibits the best electrical and optical properties [10][11][12][13][14] and is utilized in organic electronic devices such as organic light emitting diodes (OLEDs) 15 and organic photovoltaics (OPVs). 16 Therefore, it is considered as a potential organic electronic material.…”
Section: Introductionmentioning
confidence: 99%